Five Transcription Factors and FGF Pathway Inhibition Efficiently Induce Erythroid Differentiation in the Epiblast - Wei Weng; Guojun Sheng (Stem Cell Reports, 2014)
Primitive erythropoiesis follows a stereotypic developmental program of mesoderm ventralization and internalization, hemangioblast formation and migration, and erythroid lineage specification. Induction of erythropoiesis is inefficient in either ES/iPS cells in vitro or nonhemangioblast cell populations in vivo. Using the chick model, we report that epiblast cells can be directly and efficiently differentiated into the erythroid lineage by expressing five hematopoietic transcription regulators (SCL+LMO2+GATA2+LDB1+E2A) and inhibiting the FGF pathway. We show that these five genes are expressed with temporal specificity during normal erythropoiesis. Initiation of SCL and LMO2 expression requires FGF activity, whereas erythroid differentiation is enhanced by FGF inhibition. The lag between hematopoiesis and erythropoiesis is attributed to sequential coregulator expression and hemangioblast migration. Globin gene transcription can be ectopically and prematurely induced by manipulating the availability of these factors and the FGF pathway activity. We propose that similar approaches can be taken for efficient erythroid differentiation in vitro.